Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1111/0735-2166.00106
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Regional Governance under the New Regionalism: Economic Imperatives versus Political Impediments

Abstract: Over the past two decades or more, advocates of the new regionalism have called for the creation of new forms of regional governance in America. These writers have shifted the rationale for regional governance from issues of efficiency and equity that characterized an earlier literature on regionalism (i.e., the metropolitan reform school) to that of regional economic competitiveness. In this article, I examine the diagnoses and prescriptions of the metropolitan reformers and the new regionalists. I offer a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
114
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 23 publications
0
114
0
2
Order By: Relevance
“…We are guided in this paper by a definition of metropolitan governance (Norris 2001), which is slightly modified for our purposes here (see also Brenner, 2002: 5).…”
Section: Research Outlinementioning
confidence: 99%
See 3 more Smart Citations
“…We are guided in this paper by a definition of metropolitan governance (Norris 2001), which is slightly modified for our purposes here (see also Brenner, 2002: 5).…”
Section: Research Outlinementioning
confidence: 99%
“…More than a decade ago, one of the authors concluded that in the U.S. the economic premises of the New Regionalism are insufficient to overcome the political factors preventing metro reform (Norris 2001). Moreover, except for the slight hope that rescaling in Europe may bring, these factors are not likely to change and are likely to have the same effect in the future that they have had in the past -that of preventing the emergence of metro governance.…”
Section: Racial Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…These matters are constructed as distributional issues in and across metropolitan areas, including continuing sprawl, hollowing-out of the central cities of older metropolitan areas through population and tax base decentralization, traffic congestion, pollution, and the like (Orfield 1997;Norris 2001;Brenner 2002;Wheeler 2002). These policy issues just represent the new forms of sociospatial polarization and uneven geographical development that have been crystallizing in the American city-regions under contemporary conditions of postfordist urbanization and neoliberal state restructuring (Brenner 2002).…”
mentioning
confidence: 99%